Influence of Incorporation of Azolla Meal on Performance of Laying Japanese Quails - Lakshmi, R Kasi Sowjanya; Seshiah, C. Venkata; Reddy, P Ravikanth; Nagaraja, K; Kumar, I (Indian Journal of Animal Nutrition, 2019)
This study was conducted to evaluate the performance of laying Japanese quails fed on different levels of azolla meal (AZM). Ten weeks old 150 quails (Coturnix coturnix japonica) were randomly divided into 3 groups with 5 replicates of 10 birds each. Control group was fed with a diet containing 0% AZM while the other two groups received diets with 3 and 6% AZM, respectively for a period of 6 weeks. Feed consumption and egg production were recorded and feed efficiency (g feedÂ onsumed/12 eggs) was calculated during the entire trial period. Ten eggs from each treatment were examined for quality. At the end of the trial, 5 birds from each treatment group were slaughtered to study the carcass characteristics. There were no significant differences in both performance and egg quality parameters by incorporation of AZM. Carcass characteristics were also found to be similar in 3 groups except for giblet, back and wings percentage. It was concluded that AZM could be incorporated in laying quailâ€˜s diet up to 6% without affecting the performance and egg quality parameters.